OPTIMALISASI SIFAT MEKANIK MORTAR BERBASIS SILIKA AMORF SEKAM TEBU - Fitriya S (LPPM Politeknik Pratama, 2023)
Mortar is one of the materials commonly used in everyday life as part of the world of civil engineering. Cement based mortar. Where cement serves as an adhesive and reinforcement. It's just that cement has drawbacks, one of which is the raw material which is quite expensive, therefore in this study the authors made sugarcane husks which are natural wastes with SiO2 content similar to cement to optimize mortar quality. In this study, bagasse was extracted by sintering at a temperature of 4000C – 6500C so that it became amorphous silica, then passed through a 100 mesh sieve before being applied to the mortar. When operating on a mortar, variations of the addition of amorphous silica and cement are used at 0wt%, 10wt%, 20wt%, 30wt%. Identification of amorphous silica forms that occur will be analyzed using XRD. The results of the analysis showed that the addition of sugarcane husk amorphous silica had an effect on the mechanical properties of the mortar because the sugarcane husk amorphous silica could fill the pores in the mortar. The results showed that the most optimal percentage was 20 wt% with a mortar porosity of 29.54%, a compressive strength of 1.633x10-2 N/mm2 and an impact strength of 2.872x10-4 J/mm2 at an additional percentage of 20wt%.